Diabetes diagnosis and nutrition facts label use among US adults, 2005–2010. Issue 12 (20th October 2015) - An, Ruopeng
Abstract: Objective: To assess the role of diabetes diagnosis as a potential teachable moment in nutrition facts label use among US adults. Design: Logistic regression analyses were conducted to examine the relationship between diabetes diagnosis status (diagnosed diabetes, undiagnosed diabetes, diagnosed prediabetes, undiagnosed prediabetes, no diabetes or prediabetes) and self-reported nutrition facts label use, adjusted by individual characteristics and survey design. Setting: Study sample came from the National Health and Nutrition Examination Survey 2005–2010 waves. Subjects: A total of 5110 US adults aged 20 years and older were included in the analyses. Diabetes/prediabetes was identified by fasting plasma glucose and glycated Hb testing. Results: People with diagnosed diabetes/prediabetes were substantially more likely to report nutrition facts label use when making daily food purchase decisions compared with those with undiagnosed diabetes/prediabetes, whereas the prevalence of nutrition facts label use was similar between people with undiagnosed diabetes/prediabetes and those without diabetes/prediabetes. The adjusted prevalence (95 % CI) of any and regular nutrition facts label use was 85·93 (82·91, 88·95) % and 55·60 (50·04, 61·16) % among those with diagnosed diabetes, respectively, in comparison to 71·50 (59·64, 83·37) % and 32·88 (19·11, 46·65) % among those with undiagnosed diabetes. Analogously, the adjusted prevalence (95 % CI) of any and regular nutrition facts label use was 81·16 (75·27, 87·06) % and 45·28 (37·28, 53·29) % among those with diagnosed prediabetes, respectively, in comparison to 72·83 (68·06, 77·59) % and 39·95 (34·02, 45·89) % among those with undiagnosed prediabetes. Conclusions: As a potential teachable moment, diabetes diagnosis may positively impact nutrition facts label use and motivate diabetic patients to manage their condition through making healthier food choices.